TATA LAKSANA HEMANGIOMA PLEURA - Hendra Kurniawan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Hemangioma is a benign tumor in the form of very rapid proliferation of endothelial cells. The cause is thought to be due to an imbalance between proangiogenesis factors and angiogenesis inhibitor factors. Hemangiomas are more common in women than men. Hemangioma therapy can be divided into conservative therapy and active therapy. Hemangioma therapy can be divided into conservative therapy and active therapy. Treatment of pleural hemangioma can be done by surgery or excisional thoracotomy or by embolization, use of corticosteroids, and radiation therapy